Corporate social investment - bridging the digital divide. - Madhav, Natasha; Payne, Nola (My University, 2012)
The South African constitution states that "everyone has the right to education". The Skills Development Act which aims to “develop the skills of the South African workforce, improve productivity in the workplace and to promote self-employment” has had a significant impact on learning and the development of our labour force within organizations; however it has had little or no impact in reaching the many disadvantaged communities within South Africa. These communities have limited access to education and often no access to computers and the internet. The schools that do have access to technology often have limited resources. The current African National Congress (ANC) government supports the efforts by the private sector to channel finances and resources into the disadvantaged communities to improve the provision of education to these communities. Many adult learners believe that they are too old to learn how to use computers. This stems from unfamiliarity or fear of computers and technology. In order to assist learners to adapt to new technology, computers have been introduced in adult basic education and training (ABET) programmes. ABET is expected to bring about change by increasing the skills and attitudes of the disadvantaged community to make them employable or to empower them as entrepreneurs. One of the focuses of ABET is educational technology with a specific focus on information technology. The most important indicator of a population’s ability to use information technology is to apply the computer basics. It is necessary to find ways to promote the involvement of communities in computer literacy programmes. Technology learning areas provide learners with technological skills, like computer literacy. The use of technology in the work places, such as faxing, e-mail, and photocopies has replaced many employees’ manual tasks hence the acquisition of technological skills would enhance opportunities from being lower-productive and unskilled to productive high-skilled employees and this in turn will result in an increase in remuneration. Additionally, technology, as an ABET learning area, could also help learners understand technological innovations such as the use of the internet to transact electronically, obtain access to educational sites and to search for employment. The Masakhane Project’s computer literacy programme, a CSI initiative by SABMiller, offers instruction in basic computer skills, the Microsoft Office© Suite (Word, Excel, PowerPoint, and Outlook) and introductory internet usage. The authors examined the learner’s experiences of the ABET computer literacy programme on the Masakhane Project as well as the stakeholder’s contribution and have documented this in the paper. The questions asked of the community and the stakeholders was to determine a more effective and productive way of providing ABET education to achieve computer literacy amongst the community and to determine what and how similar corporate social initiatives can be improved to bridge the digital divide and at the same time improve employability. Keywords: Digital divide, technology, disadvantaged communities, stakeholders, ABET
Keywords: Technology; Digital divide; Disadvantaged communities; ABET